2021
DOI: 10.1101/2021.06.08.21258069
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bovine Colostrum Derived Antibodies Against SARS-CoV-2 Show Great Potential to Serve as a Prophylactic Agent

Abstract: Severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) until now imposes a serious burden to health systems globally. Despite worldwide vaccination, social distancing and wearing masks, the spread of the virus is still ongoing. One of the mechanisms how neutralizing antibodies (NAbs) block virus entry into cells encompasses interaction inhibition between the cell surface receptor angiotensin-converting enzyme 2 (ACE2) and the spike (S) protein of SARS-CoV-2. SARS-CoV-2 specific NAb development can be ind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Additionally, FM-CBAL74 (cow's milk fermented with the probiotic L. paracasei CBAL74) exerted a preventive action against SARS-CoV-2 [ 75 ]. In a similar vein, Kangro et al [ 76 ], reported immunoglobulins-rich colostrum after immunizing pregnant cows with SARS-CoV-2 spike protein in a surprisingly short time. Therefore, colostrum immunoglobulin preparation has a lot of potential for use in SARS-CoV-2 prevention regimens.…”
Section: Transchromosomic Bovines (Tcb's) Based Antibodiesmentioning
confidence: 81%
“…Additionally, FM-CBAL74 (cow's milk fermented with the probiotic L. paracasei CBAL74) exerted a preventive action against SARS-CoV-2 [ 75 ]. In a similar vein, Kangro et al [ 76 ], reported immunoglobulins-rich colostrum after immunizing pregnant cows with SARS-CoV-2 spike protein in a surprisingly short time. Therefore, colostrum immunoglobulin preparation has a lot of potential for use in SARS-CoV-2 prevention regimens.…”
Section: Transchromosomic Bovines (Tcb's) Based Antibodiesmentioning
confidence: 81%
“…Arenas et al have suggested that recognition of certain highly conserved motifs of viral proteins, in particular M and S2, by anti-BCoV antibodies present in milk would cause total or partial inactivation of SARS-CoV-2 [ 117 ]. Kangro and colleagues showed that the combination of antibodies derived from colostrum of cows immunized with the SARS-CoV-2 spike protein in an intranasal formulation can provide an efficient blockade against infection with SARS-CoV-2, including several of the known variants [ 118 ]. The use of bovine NAbs has previously been shown to be a potential strategy to combat HIV infections.…”
Section: The Contribution Of Animals To Immunoprophylaxis Of Covid-19mentioning
confidence: 99%
“…Recent papers reviewed the therapeutic potential of bovine Ig‐rich colostrum against SARS‐CoV‐2 32,57,58 . The impact of BIM on human health has been studied for decades (Table 3).…”
Section: Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…Recent papers reviewed the therapeutic potential of bovine Ig‐rich colostrum against SARS‐CoV‐2. 32 , 57 , 58 The impact of BIM on human health has been studied for decades (Table 3 ). Furthermore, colostrum or antibodies‐rich milk from bovines can be used against human diseases caused by viruses and bacteria, 33 , 59 where cow's milk is available to the general public.…”
Section: Severe Acute Respiratory Syndrome Coronavirusmentioning
confidence: 99%